The Description of Knowledge and Attitude of Coffee Lovers on Diabetes Melitus At Coffee Shops In Palaran District: The Description of Knowledge and Attitude of Coffee Lovers on Diabetes Melitus At Coffee Shops In Palaran District - Muhammad Ma'ruf; Arif Budi Setianto; Rindi Ibrahim Lasanudin; Sapto Yuliani (Universitas Widya Gama Mahakam Samarinda, 2023)
Background: Diabetes mellitus is a disease that is often called